Perspective on ultrashort pulse laser micromachining - Tuennermann, Andreas; Momma, Carsten; Nolte, Stefan (Applied Physics A: Materials Science and Processing, 2023)
Ultrashort pulse lasers have found widespread applications in precise micromachining. Here, we present our brief perspective on the development of this innovative technology from the 1990s until today.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Ablation; Materials processing; Micromachining; Ultrashort pulse laser